A comparison of CPT based state parameter estimates in coal boiler ash - B Wentzinger (The Australasian Institute of Mining and Metallurgy, 2021)
This paper presents the results of state parameter estimates in an active coal boiler ash storage facility using the most recent methods currently in use for cone penetrometer interpretation. State parameters estimates are also compared with the critical yield stress ratio approach, which is proposed as an additional liquefaction potential screening method. Recommendations are provided regarding additional in situ tests and laboratory tests that may be undertaken to improve the state parameter assessment and data produced for use in subsequent stability or liquefaction studies.